NdFeB계 희토류 자석 스크랩에서 에멀젼 플로우 공법을 이용한 중희토류의 용매추출 공정 연구 - 김병준(Byeong Jun Kim); 김용성(Young Sung Kim) (한국생산제조학회지, 2022)
In this study, emulsion flow equipment was newly manufactured by modifying the shape of the oil phase nozzle and the filter pore size. An experiment to find the optimal conditions for separating Nd and Dy in the chlorinated rare earth aqueous solution recovered from the dissolution process of the spent Nd magnet was performed with this equipment. The emulsion filling rate was the highest at 100% when the nozzle for spraying oil phase inside the cylinder was type B with a jaw height of 5 mm above the filter and the filter pore size was 40 to 100 μm (P2). Therefore, it was confirmed that these are the most optimal emulsion process conditions in the nozzle when separating Nd and Dy by the emulsion flow method. KCI Citation Count: 0